Probabilistic risk model to assess the potential for resistance selection following the use of anti-microbial medicated feed in pigs. Issue 7 (3rd July 2018) - Filippitzi, Maria Eleni; Chantziaras, Ilias; Devreese, Mathias; Dewulf, Jeroen
ABSTRACT: The cross-contamination of non-medicated feed with residues of anti-microbials (AM) causes a public and animal health concern associated with the potential for selection and dissemination of resistance. To analyse the associated risks, a probabilistic model was built using @Risk® (Palisade Corporation®) to show the potential extent of the effect of cross-contaminated pig feed on resistance selection. The results of the model include estimations of the proportion of pigs per production stage with residues of doxycycline, chlortetracycline, sulfadiazine and trimethoprim in their intestinal contents, as a result of exposure to cross-contaminated feed with different carry-over levels, in Belgium. By using a semi-quantitative approach, these estimations were combined with experimental data on AM concentrations associated with potential for resistance-selection pressure. Based on this model, it is estimated that 7.76% (min = 1.67; max = 36.94) of sows, 4.23% (min = 1.01%; max = 18.78%) of piglets and 2.8% (min = 0.51%; max = 14.9%) of fatteners in Belgium have residues of doxycycline in their intestinal tract due to consumption of feed with at least 1% carry-over. These values were estimated to be almost triple for sulfadiazine, but substantially lower for chlortetracycline and trimethoprim. Doxycycline concentrations as low as 1 mg/L (corresponding to consumed feed with at least 1% carry-over) can select for resistant porcine commensal Escherichia coli in vitro and in vivo . Conclusions on this risk could not be drawn for other AM at this stage, due to the lack of data on concentrations associated with resistance development. However, since the possibility of resistance mechanisms (e.g. co-selection) occurring cannot be excluded, the results of this model highlight that the use of AM medicated feed should be minimised where possible. In case of medicated feed production, good practice should be followed thoroughly at all levels of production, distribution, storage and administration, with a special focus on the feed distributed to piglets and sows.